(untitled) (The Gaze: Journal of Tourism and Hospitality, 2022)
This paper tries to find out the prospect of pilgrimage tourism at Namo Buddha, Kavre, Nepal. There is found limited academic work on pilgrimage tourism in Nepal; however, no evidence of study could be traced on Namo Buddha that is based on pilgrimage tourism perspective. A pilgrimage is an ancient form of religious travel where people make a journey to the place of their belief for experiencing spirituality. Namo Buddha is one of the sacred Buddhist shrines and important pilgrimage sites for Buddhists as they believe the relics of the previous life of Lord Buddha are kept at Namo Buddha Stūpa. Namo Buddha stūpa is also considered to be one of the holiest stūpas in Nepal including Svayambhu Stūpa (Svayambhu Mahachaitya) and the Bodhnath Stūpa (Khasti Mahachaitya). This stūpa commemorates the Buddha Śakyamuni’s sacrifice of his body to a starving tigress and her cubs in his previous life. Nepali people call this site Namo Buddha, Newars call Namo Buddha as Namura and Tibetans call it as Takmo Lu Jin. The place has a huge potential to attract both Buddhist and Hindu pilgrims including international tourists from all over the world. This place offers other attractions and activities besides pilgrimage-based elements such as sightseeing of heritage town; spectacular Himalayan ranges; paddy field terrains; hilly forests; soft adventures experience; and so on. Religious tourism and pilgrimage tourism are interchangeably used in this study and the paper is based on both the primary and secondary data. Exploratory research has been carried out to examine the religious and economic benefits of pilgrims at this site. It also tried to investigate locals’ perspectives on pilgrimage tourism development. Meanwhile, this paper not only studied prospects of pilgrimage tourism in Namo Buddha but also attempted to find out and highlight how the Covid-19 pandemic has impacted the destination.